Petrophysical Properties of Khasib Formation in East Baghdad Oil Field Southern Area - Jameel, Layth Abdulmalik; Kadhim, Fadhil S.; Al-Sudani, Hussein (Iraqi Journal of Chemical and Petroleum Engineering, 2020)
Petrophysical properties evaluation from well log analysis has always been crucial for the identification and assessment of hydrocarbon bearing zones. East Baghdad field is located 10 km east of Baghdad city, where the southern area includes the two southern portions of the field, Khasib formation is the main reservoir of East Baghdad oil field. In this paper, well log data of nine wells have been environmentally corrected, where the corrected data used to determine lithology, shale volume, porosity, and water saturation. Lithology identified by two methods; neutron-density and M-N matrix plots, while the shale volume estimated by single shale indicator and dual shale indicator, The porosity is calculated from the three common porosity logs; density log, neutron log, and sonic log, the water saturation is calculated by Indonesian model and Archie equation, and the results of the two methods were compared with the available core data to check the validity of the calculation. The results show that the main lithology in the reservoir is limestone, shale volume ranged between 0.152 to 0.249, porosity between 0.147 to 0.220, and water saturation from 0.627 to 0.966, the high-water saturation indicate that the water quantity is the determining factor of the reservoir units.